The Day I Am Free & Katitzi. - Mohtadi, Lawen; Lind, Maria (Berlin : Sternberg Press, 2019)
Hedlund, Björn
Katarina Taikon was a transformative Swedish activist, writer, and countercultural icon, anti-racist narratives, children's literature, Roma community in Sweden, Katitzi
boek
Keywords: Taikon, Katarina